Exploring the experiences of substance addicts and their families in coping with the addiction - Nalbantoğlu, İsmail and Tuncay, Tarık (Journal of Dependence, 2023)
Objective: This study aims to comprehensively understand the coping efforts of substance addicts and their family members by revealing their addiction process experiences. Method: Descriptive analysis was used in this study which was conducted through qualitative research methods. In this context, in-depth interviews were held with 13 participants, 9 of whom were addicts in recovery and 4 of their relatives. Results: This study has revealed that the effect of social environment and friends, existing problems, traumatic experiences, search for meaning, and domestic problems are among the factors leading to substance addiction. Addicted individuals are faced with social, physical, and legal issues. It was observed that the family members who learned that their relatives used substances were disappointed and sad, but they did not know enough about the treatment initiatives. Conclusion: It is considered that addiction treatment, including both the addict and the family, will increase the efficiency of the therapy and positively support the recovery process. More research is needed on the active participation of the addicts’ families in the treatment process.